A method for preparing metallographic specimen of cold-rolled metal material
By inserting non-plating waste samples in the preparation of cold-rolled metal material metallographic samples and fixing them with resin hot inlay, the problems of small observation area and uneven erosion of thin samples are solved, and the increase of the observation area of the sample and the uniform appearance of the substrate surface and internal tissue are achieved. At the same time, the acid sustained release solution prepared by modified hydrogen bond receptors and oxalic acid improves the acid etching effect and obtains a clear and complete metallographic sample.
Patent Information
- Application Number
- CN202411960808.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The cold-rolled thin samples made of coating material have a small observation area after cutting. When the thin samples are directly combined for erosion, the degree of erosion on the surface and internal substrate is not uniform, which affects the observation of the sample.
By sandwiching a piece of non-plating waste sample in the middle of the pretreated thin sample, a combined sample is formed and fixed with resin thermal inlay to increase the thickness for stable placement. At the same time, acid sustained release solution was used instead of nitric acid erosion solution, and acid sustained release solution with macromolecular network structure and adhesion properties were prepared by mixing modified hydrogen bond receptors and oxalic acid.
The problem of the difficulty of placing thin samples firmly in thermal inlay, polishing and erosion processes is solved, and the observation area of the samples is increased, ensuring uniform appearance of the substrate surface and internal tissue, and obtaining ideal erosion samples. At the same time, the use of green acid sustained release solution improves the effect of the acid etching process, clearly corrodes out the grain boundaries, and facilitates the observation of the complete crystal phase.
Smart Images

Figure CN119374995B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic sample preparation, and in particular to a method for preparing a metallographic sample of a cold-rolled metal material. Background Art
[0002] Technicians use metallographic technology to observe and analyze the internal structure of samples under high-power microscopes, so as to predict and judge the performance of materials and analyze the causes of various failures and defects. In the process of sample observation and analysis, the preparation quality of metallographic samples is particularly important; once the metallographic samples are improperly prepared, false observations will be caused, which will directly lead to wrong conclusions of analysis.
[0003] In the sample preparation process of metallographic analysis, the cross section of the sample to be observed needs to be adjusted to a plane, and it needs to be inlaid and fixed with inlay resin before being ground and polished. After forming, the sample can be easily polished and polished, and it is also conducive to the identification of microstructure under a metallographic microscope. However, after the sample of cold-rolled coated material is cut at a thinner thickness (generally a few tenths to a few millimeters), in order to achieve the observation area required by the standard, multiple thin slice sections need to be arranged side by side for inlay; however, if multiple thin samples are directly arranged and inlaid, the adjacent coated metals on the two surfaces will affect the appearance of the near-surface structure of the matrix during the corrosion process, so that it cannot be corroded to the same extent as the internal matrix. In addition, metallographic samples are often corroded with nitric acid; however, the corrosion rate of nitric acid is relatively fast, which will further aggravate the phenomenon of uneven corrosion on the surface of multiple parallel thin samples, thereby affecting the organization observation of metallographic samples within a certain range.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing metallographic samples of cold-rolled metal materials, which is used to solve the technical problems in the prior art that the thin samples of cold-rolled coated materials have a small observation area, but directly combining the thin samples for corrosion results in uneven corrosion degrees on the surface and inside of the substrate, which affects sample observation.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a metallographic sample of a cold-rolled metal material comprises the following steps:
[0008] A1. Cut hot-dip galvanized cold-rolled low-carbon steel to obtain thin specimens; the thin specimens are polished with sandpaper, wiped with alcohol, and blown dry to obtain pre-treated thin specimens;
[0009] Cold-rolled low-carbon steel grades were selected and thin specimens were obtained by cutting with a metallographic cutting machine.
[0010] A2. A piece of non-plated waste sample is sandwiched between two pre-treated thin samples to obtain a sample; 2 to 8 samples are arranged in sequence with the thickness direction as the observation surface to obtain a combined sample; the combined sample is fixed by resin hot mounting to obtain a sample;
[0011] Two pre-treated thin samples are used as cold-rolled samples, and a non-plated waste sample is placed in the middle to obtain a sample. The cross sections of multiple samples are arranged together with the same direction to obtain a combined sample. The combined sample is hot-mounted and fixed with resin to obtain a sample.
[0012] A3. The sample is subjected to coarse grinding and fine grinding in sequence on a pre-grinding machine to obtain a finely ground sample; the finely ground sample is subjected to coarse polishing and fine polishing in sequence to obtain a finely polished sample;
[0013] A4. The sample after fine polishing is etched three times with an acid slow-release solution, and then rinsed and dried with anhydrous ethanol to obtain an etched sample, which is the metallographic sample of the cold-rolled metal material prepared by the present invention;
[0014] The method for preparing the acid sustained-release solution comprises the following steps:
[0015] S1, ultrapure water, triethylenetetramine and 1,3-dichloropropanol are mixed and stirred to dissolve to obtain a reaction solution; the reaction solution is refluxed at 60-70° C. for 8-10 hours to obtain a crude product solution; the crude product solution is distilled at 80-85° C. until it is half the volume of the reaction solution to obtain a modified hydrogen bond receptor;
[0016] S2. Mix the modified hydrogen bond acceptor and oxalic acid, and stir at a constant temperature of 50-60°C for 1-1.5 hours to obtain a transparent liquid, which is the acid sustained-release liquid.
[0017] Furthermore, in step A1, the cutting size of the hot-dip galvanized cold-rolled low-carbon steel is 20 mm × 10 mm × x, wherein 0 <x≤1mm。
[0018] Furthermore, the size of the non-plated waste sample is 5mm×10mm×x, wherein 2 <x≤3mm。
[0019] Furthermore, in step A2, the resin used for hot mounting is phenolic plastic powder; the pressure value of hot mounting is 0.6-0.7 MPa, the time of hot mounting is 3-5 minutes, and the temperature of hot mounting is 130-140°C.
[0020] Furthermore, in step A3, the coarse grinding adopts reversing grinding, the speed of the pre-grinding machine during coarse grinding is 700-900r / min, and the coarse grinding time is 3-5 minutes; the fine grinding adopts reversing grinding, the speed of the pre-grinding machine during fine grinding is 1000-1400r / min, and the fine grinding time is 2-3 minutes.
[0021] Furthermore, in step A3, rough polishing adopts a polishing method of horizontal back and forth motion in a vertical rotation direction. Polishing agent and distilled water are added during the rough polishing process. The amount of polishing agent for each sample is 0.3-0.5mL, the amount of distilled water is 15-30ml, and the rough polishing time is 20-30s; during the fine polishing process, 15-20mL of distilled water is added to the sample, and the fine polishing time is 20-30s.
[0022] Furthermore, the polishing agent is a diamond spray containing a particle size of 1.5 μm.
[0023] The sample is subjected to coarse grinding and fine grinding in sequence, wherein the coarse grinding and fine grinding are both performed by reversing grinding, and the No. 1 sandpaper is rotated 90° each time to obtain a finely ground sample; the finely ground sample is subjected to coarse polishing and fine polishing in sequence to obtain a finely polished sample.
[0024] Furthermore, in step A4, the method for preparing the acid sustained-release solution comprises the following steps:
[0025] S1, ultrapure water, triethylenetetramine and 1,3-dichloropropanol are mixed and stirred to dissolve to obtain a reaction solution; the reaction solution is refluxed at 60-70° C. for 8-10 hours to obtain a crude product solution; the crude product solution is distilled at 80-85° C. until it is half the volume of the reaction solution to obtain a modified hydrogen bond receptor;
[0026] S2. Mix the modified hydrogen bond acceptor and oxalic acid, and stir at a constant temperature of 50-60°C for 1-1.5 hours to obtain a transparent liquid, which is the acid sustained-release liquid.
[0027] The reaction formula for synthesizing the modified hydrogen bond receptor by reacting the above triethylenetetramine with 1,3-dichloropropanol is as follows:
[0028]
[0029] Furthermore, in step S1, the usage ratio of ultrapure water, triethylenetetramine and 1,3-dichloropropanol is 50mL:10-15g:15-20g; in step S2, the usage ratio of the modified hydrogen bond acceptor and oxalic acid is 50-55g:25-35g.
[0030] Furthermore, in step A4, the erosion time of the acid slow-release solution is 10-20 seconds.
[0031] The present invention has the following beneficial effects:
[0032] 1. The present invention cuts cold-rolled low-carbon steel to obtain thin samples; the thickness of the cold-rolled thin samples with coated materials is relatively thin, and a combined sample is obtained by arranging the structure of pre-treated thin sample-non-coated waste sample-pre-treated thin sample. On the one hand, the combined sample solves the technical problems that thin samples are difficult to place stably and easy to tip over during the preparation process by increasing the thickness; on the other hand, the combined sample can increase the observation area of the thin sample itself, which is convenient for microscopic observation. The coated and uncoated samples are arranged and inlaid at intervals to separate the originally adjacent coated surfaces. In the etching process, the surface and internal structure of the separated cold-rolled samples are evenly displayed to obtain an ideal etched sample. The sample preparation method of the present invention is simple, and the obtained metallographic sample has a clear and complete microstructure.
[0033] 2. The present invention adopts the prepared acid slow-release liquid to replace the commonly used nitric acid etching solution. The essence of the above-mentioned acid slow-release liquid is a low eutectic solvent. Triethylenetetramine is used as a hydrogen bond acceptor and is modified by 1,3-dichloropropanol to form a modified hydrogen bond acceptor with a macromolecular network structure. The solubility of the modified hydrogen bond acceptor to oxalic acid is further increased, which can not only further increase the acidity of the prepared acid slow-release liquid, but also make the prepared acid slow-release liquid have certain adhesion properties, and can effectively remove metal ions in the acid etching process, thereby clearly corroding the grain boundaries of the composite sample, which is convenient for the later observation of the complete crystalline phase. In addition, the prepared slow-release acid solution is used as a green solvent to replace nitric acid, which also helps to practice the concept of green chemistry. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] FIG1 is an electron micrograph of a 100 μm metallographic sample of a cold-rolled metal material prepared in Example 6 of the present invention;
[0036] FIG2 is an electron micrograph of a 100 μm metallographic sample of a cold-rolled metal material prepared in Comparative Example 2 of the present invention;
[0037] FIG3 is an electron micrograph of a 100 μm metallographic sample of a cold-rolled metal material prepared in Comparative Example 3 of the present invention;
[0038] FIG. 4 is an electron micrograph of a 100 μm metallographic sample of a cold-rolled metal material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] This embodiment provides a method for preparing a slow-release acid solution for a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0042] S1. Add 50 mL of ultrapure water to a 250 mL three-necked round-bottom flask, then add 10 g of triethylenetetramine and 15 g of 1,3-dichloropropanol, stir and dissolve to obtain a reaction solution; the reaction solution is refluxed at 60°C for 8 hours to obtain a crude product solution. The crude product solution is distilled at 80°C until it is half the volume of the reaction solution to obtain a modified hydrogen bond receptor.
[0043] S2. Add 50 g of the modified hydrogen bond acceptor and 25 g of oxalic acid into a 250 mL beaker and mix well. Then transfer the beaker to an oil bath and stir at a constant temperature of 50° C. for 1 h to obtain a transparent and clear liquid, which is the acid sustained-release solution prepared by the present invention.
[0044] Example 2
[0045] This embodiment provides a method for preparing a slow-release acid solution for a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0046] S1. Add 50 mL of ultrapure water to a 250 mL three-necked round-bottom flask, then add 12 g of triethylenetetramine and 18 g of 1,3-dichloropropanol, stir and dissolve to obtain a reaction solution; the reaction solution is refluxed at 65°C for 9 hours to obtain a crude product solution. The crude product solution is distilled at 82°C until it is half the volume of the reaction solution to obtain a modified hydrogen bond receptor.
[0047] S2. Add 52 g of the modified hydrogen bond acceptor and 30 g of oxalic acid into a 250 mL beaker and mix well. Then transfer the beaker to an oil bath and stir at a constant temperature of 53° C. for 1.2 h to obtain a transparent and clear liquid, which is the acid sustained-release solution prepared by the present invention.
[0048] Example 3
[0049] This embodiment provides a method for preparing a slow-release acid solution for a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0050] S1. Add 50 mL of ultrapure water to a 250 mL three-necked round-bottom flask, then add 15 g of triethylenetetramine and 20 g of 1,3-dichloropropanol, stir and dissolve to obtain a reaction solution; the reaction solution is refluxed at 70°C for 10 hours to obtain a crude product solution. The crude product solution is distilled at 85°C until it is half the volume of the reaction solution to obtain a modified hydrogen bond receptor.
[0051] S2. Add 55 g of the modified hydrogen bond acceptor and 35 g of oxalic acid into a 250 mL beaker and mix well. Then transfer the beaker to an oil bath and stir at a constant temperature of 60° C. for 1.5 h to obtain a transparent and clear liquid, which is the acid sustained-release solution prepared by the present invention.
[0052] Example 4
[0053] This embodiment provides a method for preparing a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0054] A1. Steel type DX51D+Z was selected and cut with a metallographic cutting machine to obtain a thin sample with a length of 20mm, a width of 10mm and a thickness of 0.8mm. The thin sample was polished on 180# metallographic sandpaper. Both sides of the thin sample were polished in parallel to remove the burrs. The force should be slight to prevent damage to the surface structure. Then, the outer surface of the thin sample was gently wiped up and down with a cotton ball dipped in alcohol for 15s and blown dry to obtain the pre-treated thin sample.
[0055] A2. A 5mm×10mm×2mm non-coated waste carbon steel S50C sample is sandwiched between two pre-treated thin samples, and the cross sections are arranged side by side with the cross section facing downward to obtain a sample; two samples are closely arranged with the thickness direction as the observation surface to obtain a combined sample; the combined sample is fixed by hot mounting with resin to obtain a sample. The resin used for hot mounting is phenolic plastic powder, and the pressure value of hot mounting is 0.6MPa. At this time, the pressure indicator light of the metallographic mounting machine is red; the hot mounting time is 3 minutes, and the hot mounting temperature is 130℃.
[0056] A3. The sample is added to the pre-grinding machine for rough grinding. 400# and 800# water sandpaper are used in turn for grinding. Each time the sandpaper is rotated 90°; the speed of the pre-grinding machine is 800r / min, the force is gradually reduced, and the rough grinding time is 3 minutes to obtain the rough-ground sample. The rough-ground sample is then ground with 1200# and 1500# water sandpaper in turn for fine grinding. Each time the sandpaper is rotated 90°, and the fine grinding time is 2 minutes to obtain the fine-ground sample. The speed of the pre-grinding machine is 1000r / min, and the force is gradually reduced.
[0057] A4. The sample after fine grinding is roughly polished on a woolen polishing cloth using a polishing method of horizontal back and forth motion in a vertical rotation direction. During the rough polishing process, each sample is sprayed with polishing agent and then distilled water is added; the polishing agent is a diamond spray containing a particle size of 1.5μm, and the amount of polishing agent is 0.3mL for each sample; the amount of distilled water is 15mL, and the time for adding distilled water is 10s; the rough polishing time is 30s. At this time, there are no obvious scratches on the surface of the sample, and the rough-polished sample is obtained. The rough-polished sample is finely polished on a gold velvet polishing cloth. During the fine polishing process, 15ml of distilled water is added to each sample, and the fine polishing time is 20s to obtain the fine-polished sample. At this time, a 100x metallographic microscope is used to observe the fine-polished sample, and there are no obvious scratches on its surface.
[0058] A5. The finely polished sample was etched three times with the acid slow-release solution prepared in Example 3, each etch time was 10 seconds, at which time the surface of the finely polished sample to be observed turned dark gray, and the etched sample was obtained. The etched sample was rinsed with anhydrous ethanol for 10 seconds, and then dried to obtain a metallographic sample of a cold-rolled metal material.
[0059] Example 5
[0060] This embodiment provides a method for preparing a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0061] A1. The steel type is DX52D+Z, which is cut with a metallographic cutting machine to obtain a thin sample with a length of 20mm, a width of 10mm and a thickness of 0.5mm. The thin sample is polished on 180# metallographic sandpaper, and both sides of the thin sample are polished in parallel to remove the burrs. The force should be slight to prevent damage to the surface structure. Then, the outer surface of the thin sample is gently wiped up and down with a cotton ball dipped in alcohol for 15s and blown dry to obtain the pre-treated thin sample.
[0062] A2. A 5mm×10mm×3mm non-coated waste carbon steel S50C sample is sandwiched between two pre-treated thin samples, and the cross sections are arranged side by side with the sample facing downward to obtain a sample; 8 samples are closely arranged with the thickness direction as the observation surface to obtain a combined sample; the combined sample is fixed by hot mounting with resin to obtain a sample. The resin used for hot mounting is phenolic plastic powder; the pressure value of hot mounting is 0.7MPa, at which time the pressure indicator of the metallographic mounting machine turns red; the hot mounting time is 5 minutes, and the hot mounting temperature is 140℃.
[0063] A3. The sample is added to the pre-grinding machine for rough grinding. 400# and 800# water sandpaper are used in turn for grinding. Each time the sandpaper is rotated 90°; the speed of the pre-grinding machine is 900r / min, the force is gradually reduced, and the rough grinding time is 5 minutes to obtain the rough-ground sample. The rough-ground sample is then ground with 1200# and 1500# water sandpaper in turn for fine grinding. Each time the sandpaper is rotated 90°, and the fine grinding time is 3 minutes to obtain the fine-ground sample. The speed of the pre-grinding machine is 1200r / min, and the force is gradually reduced.
[0064] A4. The sample after fine grinding is roughly polished on a woolen polishing cloth using a polishing method of horizontal back-and-forth motion in a vertical rotation direction. During the rough polishing process, each sample is sprayed with a polishing agent and then distilled water is added. The polishing agent is a diamond spray containing a particle size of 1.5μm, and the amount of polishing agent is 0.5mL for each sample; the amount of distilled water is 15mL, and the time for adding distilled water is 10s; the rough polishing time is 30s. At this time, there are no obvious scratches on the surface of the sample, and the rough-polished sample is obtained. The rough-polished sample is finely polished on a gold velvet polishing cloth. During the fine polishing process, 20ml of distilled water is added to each sample, and the fine polishing time is 30s to obtain the fine-polished sample. At this time, a 100x metallographic microscope is used to observe the fine-polished sample, and there are no obvious scratches on its surface.
[0065] A5. The finely polished sample was etched three times with the acid slow-release solution prepared in Example 3, each etch time was 15 seconds, at which time the surface of the finely polished sample to be observed turned dark gray, and the etched sample was obtained. The etched sample was rinsed with anhydrous ethanol for 10 seconds, and then dried to obtain a metallographic sample of a cold-rolled metal material.
[0066] Example 6
[0067] This embodiment provides a method for preparing a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0068] A1. Cold-rolled deep-drawn steel DX53D+Z was selected as the steel type. It was cut with a metallographic cutting machine to obtain a thin sample with a length of 20 mm, a width of 10 mm, and a thickness of 1 mm. The thin sample was polished on 180# metallographic sandpaper. Both sides of the thin sample were polished in parallel to remove the burrs. The force should be slight to prevent damage to the surface structure. Then, a cotton ball dipped in alcohol was used to gently wipe the outer surface of the thin sample up and down for 15 seconds and blown dry to obtain the pre-treated thin sample.
[0069] A2. A 5mm×10mm×2.5mm non-coated waste carbon steel S50C sample is sandwiched between two pre-treated thin samples, and the cross sections are arranged side by side with the sample facing downward to obtain a sample; five samples are closely arranged with the thickness direction as the observation surface to obtain a combined sample; the combined sample is fixed by hot mounting with resin to obtain a sample. The resin used for hot mounting is phenolic plastic powder, and the pressure value of hot mounting is 0.6MPa. At this time, the pressure indicator light of the metallographic mounting machine is red; the hot mounting time is 4 minutes, and the hot mounting temperature is 135℃.
[0070] A3. The sample is added to the pre-grinding machine for rough grinding. 400# and 800# water sandpaper are used for reversing grinding in turn. Each time the sandpaper is rotated 90°; the speed of the pre-grinding machine is 700r / min, the force is gradually reduced, and the rough grinding time is 4 minutes to obtain the rough-ground sample. The rough-ground sample is then reversingly ground with 1200# and 1500# water sandpaper for fine grinding. Each time the sandpaper is rotated 90°, and the fine grinding time is 2 minutes to obtain the fine-ground sample. The speed of the pre-grinding machine is 1400r / min, and the force is gradually reduced.
[0071] A4. The sample after fine grinding is roughly polished on a woolen polishing cloth using a polishing method of horizontal back and forth motion in a vertical rotation direction. During the rough polishing process, each sample is sprayed with polishing agent and then distilled water is added; the polishing agent is a diamond spray containing a particle size of 1.5μm, and the amount of polishing agent is 0.4mL for each sample; the amount of distilled water is 25mL, and the time for adding distilled water is 10s; the rough polishing time is 30s. At this time, there are no obvious scratches on the surface of the sample, and the rough-polished sample is obtained. The rough-polished sample is finely polished on a gold velvet polishing cloth. During the fine polishing process, 20ml of distilled water is added to each sample, and the fine polishing time is 25s to obtain the fine-polished sample. At this time, a 100x metallographic microscope is used to observe the fine-polished sample, and there are no obvious scratches on its surface.
[0072] A5. The finely polished sample was etched three times with the acid slow-release solution prepared in Example 3, each etch time was 20 seconds, at which time the surface of the finely polished sample to be observed turned dark gray, and the etched sample was obtained. The etched sample was rinsed with anhydrous ethanol for 10 seconds, and then dried to obtain a metallographic sample of a cold-rolled metal material.
[0073] Comparative Example 1
[0074] This comparative example provides a method for preparing a metallographic sample of a cold-rolled metal material, comprising the following steps:
[0075] A1. Cold-rolled deep-drawing steel DX53D+Z was selected as the steel type. It was cut with a metallographic cutting machine to obtain a thin sample with a length of 20 mm, a width of 10 mm, and a thickness of 0.5 mm. The thin sample was polished on 180# metallographic sandpaper. There were still large flash edges on the thin sample that were not easy to polish off. Then, a cotton ball was dipped in alcohol and gently wiped the outer surface of the thin sample for 15 seconds and dried to obtain the pre-treated thin sample.
[0076] A2. No non-coated waste sample is sandwiched between the two pre-treated thin samples, and the cross sections are arranged side by side downward to obtain a single sample; the two samples are closely arranged with the thickness direction as the observation surface, and the sample is fixed by resin hot mounting to obtain a sample. The resin used for hot mounting is phenolic plastic powder, and the pressure value of hot mounting is 0.7MPa. At this time, the pressure indicator light of the metallographic mounting machine is red; the hot mounting time is 5 minutes, and the hot mounting temperature is 140℃.
[0077] A3. The sample is added to the pre-grinding machine for rough grinding. 400# and 800# water sandpaper are used in turn for reversing grinding. Each time the sandpaper is rotated 90°; the speed of the pre-grinding machine is 800r / min, the force is gradually reduced, and the rough grinding time is 5 minutes to obtain the rough-ground sample. The rough-ground sample is then reversingly ground with 1200# and 1500# water sandpaper for fine grinding. Each time the sandpaper is rotated 90°, the fine grinding time is 3 minutes, and the fine-ground sample is obtained. The speed of the pre-grinding machine is 1000r / min, and the force is gradually reduced.
[0078] A4. The sample after fine grinding is roughly polished on a woolen polishing cloth using a polishing method of horizontal back-and-forth motion in a vertical rotation direction. During the rough polishing process, each sample is sprayed with polishing agent and then distilled water is added; the polishing agent is a diamond spray containing a particle size of 1.5μm, and the amount of polishing agent is 0.4mL for each sample; the amount of distilled water is 20mL, and the time for adding distilled water is 10s; the rough polishing time is 30s. At this time, there are no obvious scratches on the surface of the sample, and the rough-polished sample is obtained. The rough-polished sample is finely polished on a gold velvet polishing cloth. During the fine polishing process, 15ml of distilled water is added to each sample, and the fine polishing time is 30s to obtain the fine-polished sample. At this time, a 100x metallographic microscope is used to observe the fine-polished sample, and there are no obvious scratches on its surface.
[0079] A5. The finely polished sample was etched three times with the acid slow-release solution prepared in Example 3, each etch time was 10 seconds, at which time the surface of the finely polished sample to be observed turned dark gray, and the etched sample was obtained. The etched sample was rinsed with anhydrous ethanol for 10 seconds, and then dried to obtain a metallographic sample of a cold-rolled metal material.
[0080] Comparative Example 2
[0081] Compared with Example 6, in this comparative example, when preparing the acid sustained-release solution, step S1 is omitted, and triethylenetetramine is used to replace the modified hydrogen bond acceptor.
[0082] Comparative Example 3
[0083] Compared with Example 6, in this comparative example, when preparing the acid sustained-release liquid, only 5 g of oxalic acid was added and mixed with the modified hydrogen bond receptor to prepare the acid sustained-release liquid.
[0084] Analysis of the accompanying drawings: By comparing and analyzing the accompanying drawings 1, 2, 3 and 4, the cold-rolled metal material metallographic sample prepared in Example 6 of the present invention has a clear and complete organizational structure, and the corrosion degree of the near-surface organization and the internal organization of the coating is uniform. However, in Comparative Example 2, the acid slow-release solution used replaces the modified hydrogen bond acceptor with triethylenetetramine, and the prepared acid slow-release solution does not form a macromolecular network structure, and the adhesion to metal ions during the acid etching process decreases; in Comparative Example 3, the acid slow-release solution used sharply reduces the amount of hydrogen bond donors, reducing the acidity of the acid slow-release solution. According to the accompanying drawings 2 and 3, it can be seen that the organizational structure of the metallographic samples prepared in Examples 2 and 3 is less apparent, and the integrity of the microstructure is reduced.
[0085] In Comparative Example 1, the pretreated thin sample was not separated by non-coated waste samples, resulting in the corrosion of the tissue near the upper and lower surfaces of the adjacent coating being affected and not being able to be displayed to the same extent as the internal tissue; according to Figure 1, it can be seen that the metallographic sample prepared in Comparative Example 1 has a sparse and unclear tissue structure.
[0086] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0087] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0088] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a metallographic sample of a cold-rolled metal material, characterized in that: The following steps are involved: A1. Cut hot-dip galvanized cold-rolled low-carbon steel to obtain thin specimens; the thin specimens are polished with sandpaper, wiped with alcohol, and blown dry to obtain pre-treated thin specimens; A2. A piece of non-plated waste sample is sandwiched between two pre-treated thin samples to obtain a sample; 2 to 8 samples are arranged in sequence with the thickness direction as the observation surface to obtain a combined sample; the combined sample is fixed by resin hot mounting to obtain a sample; A3. The sample is subjected to coarse grinding and fine grinding in sequence on a pre-grinding machine to obtain a finely ground sample; the finely ground sample is subjected to coarse polishing and fine polishing in sequence to obtain a finely polished sample; A4. The sample after fine polishing is etched three times with acid slow-release solution, then rinsed with anhydrous ethanol and dried to obtain an etched sample, which is the prepared metallographic sample of the cold-rolled metal material; The method for preparing the acid sustained-release solution comprises the following steps: S1, ultrapure water, triethylenetetramine and 1,3-dichloropropanol are mixed and stirred to dissolve to obtain a reaction solution; the reaction solution is refluxed at 60-70° C. for 8-10 hours to obtain a crude product solution; the crude product solution is distilled at 80-85° C. until it is half the volume of the reaction solution to obtain a modified hydrogen bond receptor; S2. Mix the modified hydrogen bond acceptor and oxalic acid, and stir at a constant temperature of 50-60°C for 1-1.5 hours to obtain a transparent liquid, which is the acid sustained-release liquid.
2. A method for preparing a metallographic sample of a cold-rolled metal material according to claim 1, characterized in that: In step A1, the cutting size of the hot-dip galvanized cold-rolled low-carbon steel is 20 mm × 10 mm × x, where 0 <x≤1mm。 3. A method for preparing metallographic samples of cold-rolled metal materials according to claim 1, characterized in that: In step A2, the size of the non-plated waste sample is 5mm×10mm×x, wherein 2 <x≤3mm。 4. A method for preparing a metallographic sample of a cold-rolled metal material according to claim 1, characterized in that: In step A2, the resin used for hot mounting is phenolic plastic powder; the pressure value of hot mounting is 0.6-0.7 MPa, the time of hot mounting is 3-5 minutes, and the temperature of hot mounting is 130-140°C.
5. The method for preparing a metallographic sample of a cold-rolled metal material according to claim 1, characterized in that: In step A3, the coarse grinding adopts reversing grinding, the speed of the pre-grinding machine is 700-900r / min during the coarse grinding, and the coarse grinding time is 3-5 minutes; the fine grinding adopts reversing grinding, the speed of the pre-grinding machine is 1000-1400r / min during the fine grinding, and the fine grinding time is 2-3 minutes.
6. A method for preparing metallographic samples of cold-rolled metal materials according to claim 1, characterized in that: In step A3, rough polishing adopts a polishing method of horizontal back and forth motion in a vertical rotation direction, and polishing agent and distilled water are added in sequence during the rough polishing process; the amount of polishing agent for each sample is 0.3-0.5mL, the amount of distilled water is 15-30mL, the time for adding distilled water is 10s, and the rough polishing time is 20-30s; during the fine polishing process, 15-20mL of distilled water is added to each sample, and the fine polishing time is 20-30s.
7. A method for preparing metallographic samples of cold-rolled metal materials according to claim 6, characterized in that: The polishing agent is a diamond spray containing a particle size of 1.5 μm.
8. A method for preparing metallographic samples of cold-rolled metal materials according to claim 1, characterized in that: In step S1, the usage ratio of ultrapure water, triethylenetetramine and 1,3-dichloropropanol is 50mL:10-15g:15-20g; in step S2, the usage ratio of the modified hydrogen bond acceptor and oxalic acid is 50-55g:25-35g.
9. A method for preparing metallographic samples of cold-rolled metal materials according to claim 1, characterized in that: In step A4, the erosion time of the acid slow-release solution is 10-20 seconds.
Citation Information
Patent Citations
printing and coloring process
DE888837C
Method for treating metal surfaces by carboxylation, use of the method for temporary protection against corrosion, and method for manufacturing a shaped metal sheet thus carboxylated
US20090242079A1